Immunotoxicity of Three Environmental Mycotoxins and Their Risks of Increasing Pathogen Infections - Yuhang Sun; Yuqi Song; Miao Long; Shuhua Yang (Toxins, 2023)
Aflatoxin B1 (AFB1), ochratoxin A (OTA), and deoxynivalenol (DON) are the three mycotoxins that have received the most scholarly attention and have been tested most routinely in clinics. These mycotoxins not only suppress immune responses but also induce inflammation and even increase susceptibility to pathogens. Here, we comprehensively reviewed the determining factors for the bidirectional immunotoxicity of the three mycotoxins, their effects on pathogens, and their action mechanisms. The determining factors include mycotoxin exposure doses and times, as well as species, sex, and some immunologic stimulants. Moreover, mycotoxin exposure can affect the infection severity of some pathogens, including bacteria, viruses, and parasites. Their specific action mechanisms include three aspects: (1) mycotoxin exposure directly promotes the proliferation of pathogenic microorganisms; (2) mycotoxins produce toxicity, destroy the integrity of the mucosal barrier, and promote inflammatory response, thereby improving the susceptibility of the host; (3) mycotoxins reduce the activity of some specific immune cells and induce immune suppression, resulting in reduced host resistance. The present review will provide a scientific basis for the control of these three mycotoxins and also provide a reference for research on the causes of increased subclinical infections.